The Pengaruh E-Commerce (Ojek Online), Motivasi Pelanggan Terhadap Kepuasan Pelanggan - Nathania Purnomo, Maria; Fauzi, Achmad; Yulius Caesar, Leo Andri; Suryanata, Raditya; Tombeng, Irene Yohana; Widjaya, Kania; Dipo, Maureen (Dinasti Review Publisher, 2024)
In this study we will discuss the impact of e-commerce, especially online transportation, and customer motivation, on customer satisfaction. This research will also discuss further the impact of E-Commerce (online transportation) on customer satisfaction, customer motivation on customer satisfaction and find out that E-commerce (online transportation) and customer motivation both influence customer satisfaction. This article uses quantitative research methods, where from the research results it can be seen the relationship between the use of the E-Commerce platform (online transportation), customer motivation factors, and the level of customer satisfaction.